2001
DOI: 10.1074/jbc.m106732200
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of the Sterol Carrier Protein 2 Gene in Mice Impairs Biliary Lipid and Hepatic Cholesterol Metabolism

Abstract: Hepatic up-regulation of sterol carrier protein 2 (Scp2) in mice promotes hypersecretion of cholesterol into bile and gallstone formation in response to a lithogenic diet. We hypothesized that Scp2 deficiency may alter biliary lipid secretion and hepatic cholesterol metabolism. Male gallstone-susceptible C57BL/6 and C57BL/6 Scp2(؊⁄؊) knockout mice were fed a standard chow or lithogenic diet. Hepatic biles were collected to determine biliary lipid secretion rates, bile flow, and bile salt pool size. Plasma lipo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
111
2

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(121 citation statements)
references
References 53 publications
7
111
2
Order By: Relevance
“…Overexpression of SCP-2 in L cells inhibited cholesterol efflux and increased the intracellular cholesterol pool (53), and adenoviral overexpression of SCP-2 was previously found to increase hepatic cholesterol contents (54). Conversely, liver cholesterol ester levels are reduced by 50% in SCP-2/SCP-x null mice (49) along with hypersecretion of cholesterol in bile (17,50,51). The findings in the latter two models are especially relevant, because they were obtained in vivo, although at least the second model (SCP null mice) is complicated by the concomitant alteration of L-FABP gene expression (49) mentioned above.…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of SCP-2 in L cells inhibited cholesterol efflux and increased the intracellular cholesterol pool (53), and adenoviral overexpression of SCP-2 was previously found to increase hepatic cholesterol contents (54). Conversely, liver cholesterol ester levels are reduced by 50% in SCP-2/SCP-x null mice (49) along with hypersecretion of cholesterol in bile (17,50,51). The findings in the latter two models are especially relevant, because they were obtained in vivo, although at least the second model (SCP null mice) is complicated by the concomitant alteration of L-FABP gene expression (49) mentioned above.…”
Section: Discussionmentioning
confidence: 99%
“…In its role as a transporter, this protein participates in the transportation of cholesterol inside the cell and through the cytoplasm membrane, (8,9) as well as in the rapid transportation of newly synthesized cholesterol from the endoplasmic reticulum into bile without the intervention of the cytomicrotubule system and Golgi bodies (10). Additionally, some researchers indicate that it may have a role in the biosynthesis of cholesterol, (11)(12)(13) and in the transformation of cholesterol to bile acids (14,15), cholesterol esters (16) and sterols (17). Our former findings indicated that SCP2 was overexpressed in patients with hereditary cholesterol gallstones when compared to patients with non-hereditary cholesterol gallstones, and that SCP2 may be a potential genetic factor that contributes to the formation of cholesterol gallstones (18).…”
Section: Introductionmentioning
confidence: 99%
“…At least three cholesterol binding proteins may be involved in protein-mediated cholesterol trafficking through the cytoplasm: caveolin-1, sterol carrier protein-2 (SCP-2), and liver fatty acid binding protein (L-FABP) (4,35,36). Bidirectional flux of free cholesterol and unidirectional uptake of cholesterol ester is thought to be mediated by cytoplasmic transport complexes of caveolin-1, cholesterol (or cholesterol ester), and one or more chaperone proteins (cyclophilin A, cyclophilin 40, heat shock protein 56, and/or annexin II).…”
mentioning
confidence: 99%